2014
DOI: 10.1371/journal.pone.0089912
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Gestational Stress Leads to Depressive-Like Behavior and Compromises Medial Prefrontal Cortex Structure and Function during the Postpartum Period

Abstract: Postpartum depression, which affects approximately 15% of new mothers, is associated with impaired mother-infant interactions and deficits in cognitive function. Exposure to stress during pregnancy is a major risk factor for postpartum depression. However, little is known about the neural consequences of gestational stress. The medial prefrontal cortex (mPFC) is a brain region that has been linked to stress, cognition, maternal care, and mood disorders including postpartum depression. Here we examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 73 publications
10
83
3
1
Order By: Relevance
“…Inducing aspects of maternal depression can be done in rodent models by repeated stressing of the dam prenatally [103,104] or by administering high levels of corticosterone (the primary glucocorticoid in rats) to dams during the ante-and/or post-partum periods [105,106]. Repeated stressing of dams reduced birth weight in rat offspring, particularly in male offspring [107] and high levels of corticosterone to the dam during the postpartum period can reduce weight, particularly in male offspring [106].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inducing aspects of maternal depression can be done in rodent models by repeated stressing of the dam prenatally [103,104] or by administering high levels of corticosterone (the primary glucocorticoid in rats) to dams during the ante-and/or post-partum periods [105,106]. Repeated stressing of dams reduced birth weight in rat offspring, particularly in male offspring [107] and high levels of corticosterone to the dam during the postpartum period can reduce weight, particularly in male offspring [106].…”
Section: Animal Studiesmentioning
confidence: 99%
“… With recent advances in our understanding of the gut-brain axis and the role of 5HT, we raise critical questions about how weight and growth outcomes might be related to SSRI induced changes in the GI microbiome.  Our paper provides an updated review of the literature (e.g., Leuner et al 2014;Nezvalová-Henriksen et al, 2016), with a particular focus on weight related outcomes beyond birth, developmental aspects of SSRI exposure that might also impact weight and growth, as well as provides detailed suggestions for future research. …”
mentioning
confidence: 99%
“…Chronic stress during pregnancy has also been reported to augment depressive-like behaviors in the forced swim test in lactating rats (Haim et al, 2014;Leuner et al, 2014;Smith et al, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Because pregnancy can be a very stressful time in a woman's life and depression during and after pregnancy is common [7], understanding the impact of exercise on mood states during pregnancy is important. In addition, stress and anxiety during pregnancy can contribute to postpartum depression -a serious health concern for new mothers [8]. Previous studies have found that longterm physical activity interventions/programs improve mood during pregnancy [9].…”
Section: Introductionmentioning
confidence: 99%